The influence of internal marketing on employees’ organizational commitment: evidence from small and medium retailing enterprises in Zimbabwe - Clay Hutama Basera; Marius Potgieter (Journal of the Academy of Business and Emerging Markets)
This study aims to establish the influence of internal marketing on employees' organizational commitment towards the small and medium retailing enterprise sector in Zimbabwe. The social exchange theory and the side-bet theory anchored the theoretical foundation of this study. A drop and pick-up survey strategy was used to collect data from retailing personnel. An undisguised structured questionnaire was administered to selected participants and had question items on demographics, internal marketing (rewards, training, internal communication, and empowerment), and organizational commitment. The results indicate that internal marketing variables influence the organizational commitment of SME retail employees. Implications for managers are that proper implementation of internal marketing strategies by retail SME managers can result in higher levels of employee organizational commitment, vital for organizational competitiveness.